A comprehensive educational App for propulsion systems - Tsentis, Spyros; Gaitanis, Aggelos; Gkoutzamanis, Vasilis; Kalfas, Anestis I. (American Society of Mechanical Engineers (ASME), 2024)
This paper presents the development of a multi-platform application for rapid aeroengine performance simulation which aims to reshape conventional educational processes in aerospace propulsion taught courses. This is facilitated by enhancing students’ interaction with a broad spectrum of propulsion concepts, ranging from subsonic to hypersonic regimes. The motivation of this app draws upon the ever-increasing use of smartphone apps among the student community. It is envisaged that this phenomenon could be beneficial to widen students’ knowledge. The user of the app can rapidly extract the thermodynamic and performance parameters at different operating conditions for several propulsion concepts, including conventional turbojets and turbofans, as well as ramjets, turboramjets and advanced, pre-cooled, combined cycle engines. The development process of the application as well as the built-in models are described in detail herein. The app is employed in an aeroengine technology course in Greece and used by the students to investigate the fundamental operating principles of advanced propulsion systems. These include a turboramjet, a hydrogen-powered ramjet as well as a hybrid, pre-cooled, air-breathing rocket-cycle concept. This is facilitated through the use of the app for the performance modeling of each one of the propulsive architectures. Results show that the impact of the app on the educational process is beneficial, with the vast majority of the students providing positive feedback. It is found that the app has far increased their interest and level of knowledge related to propulsion systems, in comparison to traditional teaching techniques. This would have been impossible in the time frame of an academic semester without the implementation of the app.
Keywords: 40 Engineering; 4001 Aerospace Engineering; 4010 Engineering Practice and Education; Aeroengines; Propulsion; Education; Smartphone applications